Two-Person Approaches to Studying Social Interaction in Psychiatry: Uses and Clinical Relevance - Pan, Yafeng; Cheng, Xiaojun (Frontiers in Psychiatry, 2020)
Social interaction is ubiquitous in human society. Two-person approach – a new powerful tool to study information exchange and social behaviors – aims to characterize the behavioral dynamics and neural mechanisms of real-time social interactions. In this review, we discuss the assets of two-person approaches compared to conventional single-person approaches. We describe measures and paradigms that model the social interaction in 3-D, including eye-to-eye, body-to-body, and brain-to-brain. We then discuss how these two-person measures and paradigms are used in psychiatric conditions (e.g., autism, mood disorders, schizophrenia, borderline personality disorder, and psychotherapy). Furthermore, the promise of two-person approaches (e.g., dual brain stimulation, multi-person neurofeedback) in clinical interventions is described. Finally, we discuss the methodological and translational challenges surrounding applications of two-person approaches in psychiatry, as well as prospects for future two-/multi-person studies. We conclude that two-person approaches serve as useful additions to the range of behavioral and neuroscientific methods available to assess social interaction in psychiatric settings, involving both diagnosis and complementary interventions.